Synthesis of CaFe2O4-NGO Nanocomposite for Effective Removal of Heavy Metal Ion and Photocatalytic Degradation of Organic Pollutants - Manmeet Kaur; Manpreet Kaur; Dhanwinder Singh; Aderbal C. Oliveira; Vijayendra Kumar Garg; Virender K. Sharma (Nanomaterials, 2021)
This paper reports the successful synthesis of magnetic nanocomposite of calcium ferrite with nitrogen doped graphene oxide (CaFe2O4-NGO) for the effective removal of Pb(II) ions and photocatalytic degradation of congo red and p-nitrophenol. X-ray diffraction (XRD), Fourier transform infrared (FT-IR), transmission electron microscopy (TEM), and scanning electron microscopy-energy dispersive X-ray (SEM-EDX) techniques confirmed the presence of NGO and CaFe2O4 in the nanocomposite. The Mössbauer studies depicted the presence of paramagnetic doublet and sextet due to presence of CaFe2O4 NPs in the nanocomposite. The higher BET surface area in case of CaFe2O4-NGO (52.86 m2/g) as compared to CaFe2O4 NPs (23.45 m2/g) was ascribed to the effective modulation of surface in the presence of NGO. Adsorption followed the Langmuir model with maximum adsorption capacity of 780.5 mg/g for Pb(II) ions. Photoluminescence spectrum of nanocomposite displayed four-fold decrease in the intensity, as compared to ferrite NPs, thus confirming its high light capturing potential and enhanced photocatalytic activity. The presence of NGO in nanocomposite offered an excellent visible light driven photocatalytic performance. The quenching experiments supported ●OH and O2●− radicals as the main reactive species involved in carrying out the catalytic system. The presence of Pb(II) had synergistic effect on photocatalytic degradation of pollutants. This study highlights the synthesis of CaFe2O4-NGO nanocomposite as an efficient adsorbent and photocatalyst for remediating pollutants.